2017
DOI: 10.21873/anticanres.11946
|View full text |Cite
|
Sign up to set email alerts
|

Anti-proliferative, Cytotoxic and NF-ĸB Inhibitory Properties of Spiro(Lactone-Cyclohexanone) Compounds in Human Leukemia

Abstract: Results show that compound and compound have potential as anti-cancer agents. In addition, compound exerted NF-kB inhibition activity in leukemia cancer cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Spiroheterocyclic scaffolds have evoked immense research interest in the area of synthetic organic chemistry and medicinal chemistry [1,2] since they incorporate the ubiquitous substructures present in a broad range of bioactive natural isolates and synthetic compounds [3]. They possess a wide spectrum of useful properties, such as anti-cancer [4][5][6][7], acetylcholinesterase (AChE) inhibition [8,9], anti-proliferative [10,11], antimicrobial [12,13], photochromism [14][15][16], and holetransporting abilities [17]. One major advantage that spiroheterocycles offer as core structures is their structural rigidity and inherent structural complexity and ability to project functionality in all three dimensions [2,18], which provides an enhanced affinity to biotargets [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…Spiroheterocyclic scaffolds have evoked immense research interest in the area of synthetic organic chemistry and medicinal chemistry [1,2] since they incorporate the ubiquitous substructures present in a broad range of bioactive natural isolates and synthetic compounds [3]. They possess a wide spectrum of useful properties, such as anti-cancer [4][5][6][7], acetylcholinesterase (AChE) inhibition [8,9], anti-proliferative [10,11], antimicrobial [12,13], photochromism [14][15][16], and holetransporting abilities [17]. One major advantage that spiroheterocycles offer as core structures is their structural rigidity and inherent structural complexity and ability to project functionality in all three dimensions [2,18], which provides an enhanced affinity to biotargets [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…The worldwide study on anticancer drugs revealed complex interactions. The anticancer activity can be associated with the induction of apoptosis and inhibition of STAT3 and NF-κB transcription factors activation via oxidative stress [36,37]. For numerous sesquiterpene lactones the cytotoxic activity is related to the presence of α-methylene group in the γ-lactone ring or α,β-unsaturated ketone which can function as a Michael acceptor and interact through nucleophilic attack with the SH group of proteins, GSH and nitrogen bases, mainly guanine [36,38].…”
Section: Resultsmentioning
confidence: 99%
“…It is commonly accepted that the small-molecule inhibition of nuclear factor-κB (NF-κB) is quite an interesting strategy to improve cancer chemotherapy. In this field of research, our group reported collaborative work in the anti-proliferative, cytotoxic, and NF-κB inhibitory properties of spiro(lactone-cyclohexanone) synthetic compounds in human leukemia [44]. The spiro(lactone-cyclohexanone) derivatives 44 and 45 (Figure 21) were revealed as the most effective in the inhibition of the proliferation of the human leukemia cell lines K562 and U937, with IC 50 values of 74.02 ± 4.10 µM (K562) and 51.6 ± 4.2 µM (U937) for the derivative 44, and 58.6 ± 4.2 µM (K562) and 43.7 ± 1.5 µM (U937) for compound 45 [44].…”
Section: Anticancer Activitymentioning
confidence: 99%
“…Pharmaceuticals 2023, 16, x FOR PEER REVIEW 14 of 29 research, our group reported collaborative work in the anti-proliferative, cytotoxic, and NF-ĸB inhibitory properties of spiro(lactone-cyclohexanone) synthetic compounds in human leukemia [44]. The spiro(lactone-cyclohexanone) derivatives 44 and 45 (Figure 21) were revealed as the most effective in the inhibition of the proliferation of the human leukemia cell lines K562 and U937, with IC50 values of 74.02 ± 4.10 µM (K562) and 51.6 ± 4.2 µM (U937) for the derivative 44, and 58.6 ± 4.2 µM (K562) and 43.7 ± 1.5 µM (U937) for compound 45 [44]. Additionally, the spiro(lactone-cyclohexanone) 44 was also capable of reducing TNFα-stimulated NF-ĸB activation, with an IC50 of 15.9 ± 4.0 µM [44].…”
Section: Anticancer Activitymentioning
confidence: 99%
See 1 more Smart Citation